On the frontiers of climate and environmental change : vulnerabilities and adaptations in central Vietnam - Casse, Thorkil; Bruun, Ole (Environmental Science and Engineering, Environmental Engineering, 2013)
This book is intended to fill a gap in climate-change literature by providing a comprehensive regional study and identifying the overall adaptation challenges in a real-life context. The way in which possible climate impacts interact with a range of other challenges in agriculture, forestry, disaster planning, health care, general economic development, and common livelihoods are presented, and it is argued that greater realism and broader vision are needed in order to address the climate challenge. For instance, unsuitable land- use changes in both coastal and highland regions may increase the vulnerability of rural people, many of whom are already living on the fringes. The author(s) also state(s) that, depending on context, it may be pertinent to address short-term and unsustainable resource use, irregularities in local land management, ineffective governance and social inequality, which are all likely to aggravate the impact of external climate and weather. Not least, it is imperative to integrate general environmental management with any climate-change adaptation effort.